2017
DOI: 10.1007/s10067-017-3721-7
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic classification of anti-neutrophil cytoplasmic antibody-associated glomerulonephritis: achievements, limitations, and perspectives

Abstract: Clinical and histological factors have been identified as predictors of early and late renal outcome in ANCA-associated vasculitides (AAV). The presence and severity of kidney involvement at diagnosis are associated with poor prognosis in both patient and renal survival. Histologic findings remain the gold standard for diagnosing patients with AAV. In order to quantify the extent of the morphological parameters in the renal biopsies and to identify the histopathological lesions that predict renal outcome, seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Generally, the most clinically valuable prognostic models are those that can be used to guide physicians regarding treatment and follow-up regimens for patients [ 31 , 32 ]. If left untreated, a patient with ANCA-GN has a very poor prognosis [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the most clinically valuable prognostic models are those that can be used to guide physicians regarding treatment and follow-up regimens for patients [ 31 , 32 ]. If left untreated, a patient with ANCA-GN has a very poor prognosis [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kidney disease is common in AAV, and the typical renal presentation is rapidly progressive. Histologically, pauci-immune necrotizing crescentic glomerulonephritis is the most typical pathological characteristic, and histologic findings remain the gold standard for diagnosing patients within ANCA-associated renal vasculitis ( 4 ). Our results found that the more severe the RVLs, the lower the proportion of normal glomeruli, and that the higher the proportion of global glomerulosclerosis, the higher the scores of interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The kidney is the most common organ involved in AAV, and more than 75% of patients with AAV have renal involvement and missed or delayed diagnosis may endanger the life of a patient ( 1 3 ). In 2010, a new histopathological classification was proposed, which included four major categories, foci, mixed, crescent colored, and sclerosis, and provided valuable information to clinicians ( 4 ). However, the classification is based only on glomerular lesions, and parameters of renal interstitial vascular lesions are excluded.…”
Section: Introductionmentioning
confidence: 99%
“…Glomerular changes appear in the form of extensive crescent glomerulonephritis, while immunofluorescence microscopy shows a pauci-immune pattern. Pathohistological changes in the glomeruli are classified according to their frequency and extent, crescent count, and the presence of glomerular sclerosis ( 6 , 7 ). Vasculitis is the cause of rapidly progressive glomerulonephritis in about 80% of the cases ( 2 ).…”
mentioning
confidence: 99%